A new species of Mesacturoides Manning, 1978 (Stomatopoda: Takuidae) from the Arabian Sea - Hwang, Hee-Seung; Rouse, Greg W. (Zootaxa, 2026)
This study describes Mesacturoides dewysea sp. nov., a new species of takuid mantis shrimp discovered in the coastal waters of Oman. The new species is characterized by a distinctive combination of morphological features, including numerous telson spiniform denticles (22–38 submedian and 8–27 intermediate denticles), a completely ovate telson median boss, and a large uropodal endopod bearing a dense patch of setae on the anterior margin of the ventral surface. Among the three known species of Mesacturoides, M. dewysea sp. nov. is morphologically most similar to M. fimbriatus (Lenz, 1905), sharing the aforementioned combination of characters and exhibiting an overlapping range in telson spiniform denticle number associated with growth. However, careful examination of specimens of comparable size demonstrates that the new species is consistently distinguished by the complete absence of accessory median carinae on the telson. As a result, the genus Mesacturoides currently comprises four species, including the new species described herein. Additionally, a key to the known species of the genus is provided.